How the Working Memory functioning? Influences in learning of children with typical development and development coordination disorder - Zanella, Larissa W.; Valentini, Nadia C. (Medicina (Ribeirao Preto), 2016)
Children with learning disabilities may have limitations on the ability to store and / or organize information properly handled and need for implementation of school and / or motor tasks. Working memory, also called short-term memory, cognition is a variable widely investigated in recent years. The objectives of this systematic literature review were: (1) verify the function of the components of working memory in school-age children; (2) verify the influence of working memory in cognitive performance and learning difficulties of children of school age; (3) verify the limitations of working memory in children with Developmental Coordination Disorder. The search for articles occurred between February and May 2013. The PubMed and EBSCO data, resulting in a total of 60 included articles were used. Working memory affects the learning and specific deficits are observed in school-age children with learning difficulties as well as in children with Developmental Coordination Disorder